2015
DOI: 10.1164/rccm.201409-1615oc
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Endobronchial Ultrasound–guided Transbronchial Needle Aspiration under General Anesthesia versus Moderate Sedation

Abstract: Rationale: Data about the influence of the type of sedation on yield, complications, and tolerance of endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) are based mostly on retrospective studies and are largely inconsistent.Objectives: To determine whether the type of sedation influences the diagnostic yield of EBUS-TBNA, its complication rates, and patient tolerance.Methods: Patients referred for EBUS-TBNA were randomized (1:1) to undergo this procedure under general anesthesia (GA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
136
3
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(159 citation statements)
references
References 11 publications
10
136
3
5
Order By: Relevance
“…Our data prove that EBUS-TBNA under conscious sedation is associated with extremely high patient satisfaction, in agreement with previous reports, including studies that used different agents for conscious sedation [16,24,27].…”
Section: Original Articlesupporting
confidence: 93%
See 3 more Smart Citations
“…Our data prove that EBUS-TBNA under conscious sedation is associated with extremely high patient satisfaction, in agreement with previous reports, including studies that used different agents for conscious sedation [16,24,27].…”
Section: Original Articlesupporting
confidence: 93%
“…A recent randomized trial on 149 patients is in agreement with our experience since it concluded that EBUS-TBNA performed under moderate sedation results in comparable diagnostic yield, rate of major complications, and patient tolerance as under general anesthesia [24]. …”
Section: Original Articlesupporting
confidence: 87%
See 2 more Smart Citations
“…A previous report showed that EBUS-TBNA performed under moderate sedation with a combination of fentanyl and midazolam resulted in comparable diagnostic yield, major complication rate and patient tolerance values compared with those who received general anesthesia (13). EBUS-TBNA with endobronchial intubation was performed in 24 patients in this post hoc analysis.…”
Section: Discussionmentioning
confidence: 92%